Peer tutoring to improve writing competence in primary education - Mariona Corcelles-Seuba; Jesús Ribosa; Patricia Jara Calaforra-Faubel (Revista Española de Pedagogía, 2025)
Knowing how to write is essential for academic success and lifelong learning. This study presents and evaluates an innovative peer tutoring programme (“Reading and writing in pairs”) for improving the writing skills of primary school students. A pre-test-post-test design was used to assess improvements in the writing skills of 75 students from years five and six of primary education, and a descriptive design was used to analyse teachers’ and students’ perceptions of peer tutoring. The results showed significant improvements in all dimensions of writing skills apart from grammar. According to the participants’ evaluations, these improvements can be attributed to the highly structured organisation of the programme’s writing activity and effective interaction between tutor and tutee. Students and teachers alike reported an increase in motivation towards writing. However, two key challenges were identified for effective peer-tutoring practice: initial training for the role of tutor, and support for text revision and preparation of improvements activities by the tutor. In conclusion, the study’s results suggest that sharing the teaching role with students through peer tutoring can be an effective way to motivate and improve writing skills in primary education.